BEYOND “HE” AND “SHE”: A CRITICAL DISCOURSE ANALYSIS OF LINGUISTIC EQUITY AND NON-BINARY GENDER REPRESENTATION IN EFL TEXTBOOKS - Rizki Fauzi; Miku Fujita; Emily Thompson (Yayasan Adra Karima Hubbi, 2025)
Scholarship has long critiqued gender imbalance in English Language Teaching (EFL) materials, yet a significant gap persists regarding identities outside the gender binary. Textbooks often reinforce a cisnormative worldview, failing to reflect contemporary linguistic and social realities. This study critically analyzes the discursive practices constructing gender representation, focusing on the exclusion of non-binary identities and the status of linguistic equity in widely-used EFL textbooks. A Critical Discourse Analysis (CDA) was employed, examining a corpus of three major, globally-distributed EFL textbook series. The analysis integrated quantitative pronoun frequency counts (“he”, “she”, singular “they”) with qualitative and semiotic analysis. Findings reveal a systemic “binary-only entrenchment.” Despite quantitative parity between “he” and “she”, there was a zero-occurrence of the singular “they” for human reference. This erasure is actively maintained through discursive avoidance (e.g., “he or she”) and reinforced by stereotypes, amounting to symbolic annihilation. The analyzed textbooks are not merely outdated but actively perpetuate a hegemonic, binary-exclusive ideology. This failure in linguistic equity misprepares learners and constitutes a significant ethical and pedagogical lapse in the ELT industry.